Rancang Bangun REST API Aplikasi Sistem Informasi Gardu Distribusi berbasis Android dan Web - Sofy Fitriani; Muhammad Rizqi Sholahuddin; Siti Dwi Setiarini (Journal of Information System Research (JOSH), 2022)
Today, the use of information systems is important, especially in archiving important data. Advances in technology have made conventional recordings begin to switch to digital. The case study in this research is to make an information system on one of the electric power systems, namely the distribution system. In this distribution system there is a substation that contains important components in the distribution of electricity from transmission to consumers. Generally, data collection at distribution substations uses manual recording on paper. This becomes less effective when it finds conditions of archiving data that have been in the past. Therefore, an application is designed that can help the authorities to record android-based data and websites. This information system is made using Rest API which facilitates communication via the internet. From the research that has been done, the performance between the mobile application and the website is good. Website performance produces applications on the web that have good results, namely 99, while Android is 93 from a maximum value of 100.